OPINI DAN STATUS TINDAK LANJUT REKOMENDASI BADAN PEMERIKSA KEUANGAN PADA PEMERINTAH DAERAH DI KALIMANTAN BARAT, TENGAH, DAN TIMUR - Purba, Charles Bohlen (Jurnal Akuntansi, 2014)
The objectives of this study are to analyze and map the progress of the opinion on LKPD as well as to analyze the follow-up status of the BPK recommendation based onÂ the BPK assesment result. The methodology of this research uses bivariate correlation,Â map of markers radar, and histogram analysis. The opinion on LKPD showed positive andÂ significant progress in West Kalimantan from 2007 to 2008 and in 2009 ; also in CentralÂ Kalimantan from 2007 to 2008 as well as in 2010 and 2011 ; and in East KalimantanÂ from 2007 to 2008 as well as in 2010 and 2011 . The map of the opinions on LKPD inÂ West Kalimantan changed from narrow zigzag in 2007-2009 into a stable wide trend in 2011 (13 of 15 entities in the circle of the three maps), whereas in Central and East Kalimantan remained zigzag up to 2011. The status â€œfollowed up as recommendedâ€ wasÂ given by BPK to the three studied regions; West Kalimantan with approximately 3,007Â cases which amounted 68.336 billion rupiah , Central Kalimantan with 3,800 cases whichÂ was equal to 126.569 billion rupiah, and finally East Kalimantan with 2,350 cases whichÂ resulted in 202.01 billion rupiah and USD 1,126,272,000. Conclusion in West Kalimantan,Â Central Kalimantan, East Kalimantan The Opinion on LKPD have Developed in aÂ Positive.